Perbandingan Kebijakan Sistem Big Data Di Indonesia Dan Uni Eropa - Tanzil Kurmiawan; Anang Setiyawan; Woro Winandi (Widya Yuridika, 2020)
Human rights are individual privacy that must or must be protected by the state and recognized internationally. Privacy protection is regulated in article 28 G paragraph (1) of the 1945 Constitution. Government regulations in Indonesia are quite a lot in regulating individual privacy on personal data but have not been firm enough and clear in regulating the protection and confidentiality of individual privacy, especially those stored in big data. The development of big data in Indonesia is very rapid somany parties have taken advantage of business by managing the data of Indonesian citizens in the system he made. However, this has not been matched by regulatory reforms and the existence of legal certainty over information security standards applied in the big data system so that the data owner suffers a loss if there is a violation of his personal data. The results of this study are comparing and analyzing the regulations in force in Indonesia with the General Data Protection Regulations which have effectively been in effect in the European Union since 2018.